Zephyr.Co ( Naturally In Every Drop) / Amiesya Sofina Mohd Fuad - Amiesya Sofina, Mohd Fuad (2020)
Zephyr.Co is a company that provides a full range of services with the highest design quality in the world, and expect to be developing aroma products to designing spaces that possess natural scents. The concept of the company is to let people admire the qualities of natural fragrances, draw out the latent powers, helps people with anxiety, to calm themselves, and most important thing, every production of the product is environmentally friendly. The product that we serve are personal automatic home diffuser together with essential oils where the customer may purchase it either by buying the whole set or buying them separately. The personal automatic home diffuser bottle is made with the most durable and high-quality materials while the essential oils are made from premium natural scent that comes from a variety of flowers and fruits. Through some observation, we can summarize that there are a few categories that suit to be our potential customers. Among them are based on gender and age, by customer’s income, by customer’s lifestyle preference, and lastly, by purchasing cycle. These individuals are the customers who are most likely to use this company's products and services. No exception, this kind of business also have their own competitive advantage. For Zephyr.Co, valued price is one of the advantages. This company is providing a product that is basic but serves the purpose well. Another one is, premium offer. Zephyr.Co provide a product that offers desirable benefits to dearest customers. Lastly, custom made solutions where the company draws on its expertise and assembles resources to provide a unique solution to the problem. Undeniable, Zephyr.Co has the ability to gain sufficient profit to ensure our business continues to roll without any issues. All the profit we gained is what we got after all the expenses directly related to the production of our products have been paid. A sufficient profit will be used to upgrade the diffuser’s quality itself to ensure our customer is satisfied with the result.